Genetic Basis of Gluten Aggregation Properties in Wheat (Triticum aestivum L.) Dissected by QTL Mapping of GlutoPeak Parameters - Zhou, Zhengfu; Zhang, Ziwei; Jia, Lihua; Qiu, Hongxia; Guan, Huiyue; Liu, Congcong; Qin, Maomao; Wang, Yahuan; Li, Wenxu; Yao, Wen; Wu, Zhengqing; Tian, Baoming; et al. (Frontiers in Plant Science, 2021)
Bread wheat is one of the most important crops worldwide, supplying approximately one-fifth of the daily protein and the calories for human consumption. Gluten aggregation properties play important roles in determining the processing quality of wheat (Triticum aestivum L.) products. Nevertheless, the genetic basis of gluten aggregation properties have not been reported so far. In this study, a recombinant inbred line (RIL) population derived from the cross between Luozhen No.1 and Zhengyumai 9987 was used to identify quantitative trait loci (QTL) underlying gluten aggregation properties with GlutoPeak parameters. A linkage map was constructed based on 8518 SNPs genotyped by specific length amplified fragment sequencing (SLAF-seq). A total of 33 additive QTL on 14 chromosomes were detected by genome-wide composite interval mapping (GCIM), four of which accounted for more than 10% of the phenotypic variation across two environments. Two major QTL clusters were identified on chromosomes 1DS and 1DL. A premature termination of codon (PTC) mutation in the candidate gene (TraesCS1D02G009900) of the QTL cluster on 1DS was detected between Luozhen No.1 and Zhengyumai 9987, which might be responsible for the difference in gluten aggregation properties between the two varieties. Subsequently, two KASP markers were designed based on SNPs in stringent linkage with the two major QTL clusters. Results of this study provide new insights into the genetic architecture of gluten polymerization properties in wheat, which are helpful to future improvement of the processing quality in wheat breeding.